Building Better Biology Undergraduates through Information Literacy Integration. - Brian Winterman (Issues in Science and Technology Librarianship)
Biology undergraduates at Indiana University have often been expected to find information for course exercises or written reports, but the skills necessary to do so are not taught consistently in the curriculum. Other efforts described in the literature have been successful in teaching information literacy skills, but not always in a way that is embedded in the content of the discipline. In this paper the author discusses how collaboration with biology researchers and professors lead to the development of a course to teach biology undergraduates information literacy skills in the context of the research process. [ABSTRACT FROM AUTHOR]